Pro LCS Live Communications Server Administration - Maximo, Rui; Edney, Andrew (Apress : Imprint: Apress, 2007)
Pro LCS: Live Communications Server Administration will guide you on how to best leverage Microsofts Live Communications Server 2005 (LCS) to improve your business communications. This information-packed volume includes everything you need to know about LCS, but were afraid to ask. This includes all the different clients that you can utilize and how you can best deploy them. This book comes loaded with handy hints and tips, useful real-world scenarios, and extensive walkthroughs aimed at getting you up and running as quickly and painlessly as possible. It even includes a complete discussion about setting up a pilot deployment and rolling out the final solution in your chosen environment. This book is the expert guide to LCS for administrators, systems integrators, architects, and product or project managers who want to get the most out of LCS. Create code art, visualizations, and interactive applications with this powerful, yet simple computer language and programming environment Learn how to code 2D and 3D animation, pixel-level imaging, motion effects, and physics simulations Take a creative and fun approach to learning creative computer programming.